EVALUASI PELAKSANAAN PROGRAM REHABILITASI PENYANDANG CACAT - Lilis Wahyuni (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Evaluation of Rehabilitation of Disabled Persons Program. This study aimed to evaluate the implementation of the Disabled Rehabilitation Program at the Department of Social Dumai. This research is a descriptive study with qualitative approach. Informants in this study are those that play a role in the implementation of the Disabled Rehabilitation Program at the Department of Social Dumai. Data collection technique were interview, observation and documentation. Analysis of data through data reduction, data presentation and conclusion. The results showed that the implementation of the Rehabilitation of Persons with Disabilities Program in Social Service Dumai seen from indicators of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy, there are still many shortcomings. None of the evaluation indicators used can be fulfilled in the Implementation of the Programme of Rehabilitation of Persons with Disabilities on Social Department Dumai.